The Impact of Work Method on Musculoskeletal Disorders Complaints in Pharmacy Unit - Nasution, Achmad Delianur; Mahyuni, Eka Lestari (Disease Prevention and Public Health Journal, 2020)
Background: Musculoskeletal disorders (MSDs) are complaints on parts of skeletal muscle which is perceived by someone ranging from mild to severe. These complaints often occur in the manual process, heavy workload, and work environment interactions that may lead to a non-ergonomic work posture. This study aims to analyze the impact of the work method to MSDs complaints at the pharmacy unit of The University of Sumatera Utara Hospital. Method: This study is an observational survey using a cross-sectional design. The population was all workers in the pharmacy unit of the University of Sumatera Utara Hospital numbered 27 people. Samples were taken from the total population. Data were collected using camera media and direct observation of the work process that took place in the pharmacy unit of USU Hospital. Musculoskeletal complaints were obtained by mapping the pain using Nordic Body Map (NBM). The data obtained were analyzed using a simple logistic regression test to see the impact of the working methods of the pharmacy unit workers on their complaints of musculoskeletal disorders. Results: There was a significant association between work methods in the Pharmacy unit and the MSDs complaints with p-value = 0,001. This was supported by the mean of the work patterns in the pharmacy unit which have a heavy workload and the interaction with the layout according to anthropometry. There was a significant association between the work method causing musculoskeletal complaints when the drug compounding process (p = 0.000). It was evidenced from the result of NBM questionnaire that the three most prevalent complaints of MSDs were pain around the neck, back, and right shoulder. Conclusion: It can be concluded that the static working methods with a heavy workload must be accompanied by a relaxation to avoid burn out and fatigue.